Case Report: A case report of unstable Hangman fracture in a eighty year old male [version 2; referees: 2 approved, 1 not approved] - Sunil Munakomi; Binod Bhattarai (F1000Research, 2015)
Herein we discuss a rare variant of hangman’s fracture in an eighty year old male with good Karnofsky performance score. We performed X-ray and magnetic resonance imaging (MRI) of the cervical spine to confirm the diagnosis. The patient was placed on a gentle cervical traction which showed good reduction. Despite being on a resource limited setup,  we performed posterior occipitocervical fusion with bone graft fusion followed by early mobilization. A postoperative scan showed good reduction and purchase of the screws. This case highlights the importance of choosing the correct therapeutic attitude for the management of the geriatric population especially in those who do not have any significant co-morbid conditions.